(untitled) (Bangladesh Journal of Medicine, 2019)
Hydrocephalous is a rare manifestation of systemic lupus erythematosus. Cerebral venous thrombosis, immune complex deposition within the arachnoid villi or direct post-inflammatory lesions of the central nervous system are possible causes of developing acute hydrochephalus. We report a case of acute non-communicating hydrocephalus secondary to stenosis of the aqueduct of Sylvius. The condition developed rapidly in a 22-year-old woman with previously diagnosed SLE. Bangladesh J Medicine Jan 2020; 31(1) : 33-36